The Role of Judiciary and Police in Juvenile Delinquency: A Comprehensive Examination - Majeed, Mudassir; Parveen, Abida; Zahoor, Muhammed Ashraf (Annals of Human and Social Sciences, 2024)
The main objective of this research paper is to investigate the multifaceted roles of the judiciary and police in addressing juvenile delinquency and its underlying causes. Juvenile delinquency poses significant challenges to society, impacting youth development, public safety, and community well-being. The judiciary and police play crucial roles in addressing this issue by enforcing laws, providing rehabilitation and prevention programs, and fostering collaboration. A comprehensive review of literature, case studies, and empirical research was conducted to examine the policies, practices, and outcomes related to juvenile delinquency intervention by the judiciary and police. Findings of the revealed that both the judiciary and police have distinct, yet complementary roles in addressing delinquency. The judiciary focuses on adjudicating cases, imposing sanctions and providing rehabilitative services. The police play a vital role in prevention, early intervention, and community partnerships. Collaboration and coordination between these agencies are essential for effective and comprehensive intervention. Policymakers, practitioners, and stakeholders are encouraged to prioritize evidence-based approaches that address the root causes of juvenile delinquency. This includes early intervention programs, community-based policing, restorative justice practices, and tailored rehabilitation programs. Strengthening collaboration between the judiciary and police, as well as involving community organizations, is crucial for reducing recidivism and promoting positive youth development.